Sustainable Transport New Trends and Business Practices - Golinska, Paulina; Hajdul, Marcin; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
The aim of the book is to present the emerging environmental issues in organization and management of transport logistics. The scope of the book includes set of solutions which show different stakeholders$1 (Bviewpoints on sustainability. It points out how the transport operations organized and conducted in companies and regions might be consistent with the concept of sustainable development. The scope of the book takes into consideration trade-off relations between actors directly and indirectly involved in transport networks. Therefore, the authors present, in individual chapters, innovative approach to eco-friendly organization and coordination of transport processes, as well as management of transport networks.s
On the way to sustainability in the transport sector -- Collaboration models for sustainable transport -- Information systems and information management supporting sustainable transport -- Intermodal transport and models for CO2 reduction.
Keywords: Environmental sciences; Biotechnology; Sustainable development; Environment; Environmental Engineering/Biotechnology.; Sustainable Development; Production/Logistics/Supply Chain Management